Plant Polysaccharides-Based Multiple-Unit Systems for Oral Drug Delivery - Nayak, Amit Kumar; Hasnain, Md Saquib; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book explores the use of various plant polysaccharides for pharmaceutical purposes, including drug delivery. It examines the exploitation of plant polysaccharides' auxiliary functions to enhance drug release, stability, bioavailability and target specificity. Plant-derived materials are at the center of drug-delivery research thanks to their non-toxicity, biodegradability, ready availability, eco-friendliness and low extraction costs. These materials include polysaccharides, a class of naturally occurring polymers consisting of glucose monomers, which serve as storage carbohydrates in cereals, root vegetables, rhizomes, seeds, fruits, etc.
Introduction: multiple-unit systems for oral drug delivery -- Plant polysaccharides in drug delivery -- Locust bean gum-based multiple-unit systems for oral drug delivery -- Xanthan gum-based multiple-unit systems for oral drug delivery -- Sterculia gum-based multiple-unit systems for oral drug delivery -- Tamarind polysaccharide-based multiple-unit systems for oral drug delivery -- Guar gum-based multiple-unit systems for oral drug delivery -- Psyllum polysaccharide-based multiple-unit systems for oral drug delivery -- Cashew gum-based multiple-unit systems for oral drug delivery -- Fenugreek polysaccharide-based multiple-unit systems for oral drug delivery -- Okra gum-based multiple-unit systems for oral drug delivery -- Gum kondagogu-based multiple-unit systems for oral drug delivery -- Starch-based multiple-unit systems for oral drug delivery -- Conclusion.
Keywords: Biomaterials; Pharmaceutical chemistry; Chemistry, Organic; Botanical chemistry; Biomaterials; Pharmaceutics; Organic Chemistry; Plant Biochemistry